Mechanical properties of a polylactic 3D-printed interim crown after thermocycling - Re-Mee Doh; Won-Il Choi; Seo Young Kim; Bock-Young Jung (PLoS ONE, 2025)
Polylactic acid (PLA) has garnered attention for use in interim dental restorations due to its biocompatibility, biodegradability, low cost, ease of fabrication, and moderate strength. However, its performance under intraoral conditions, particularly under heat and moisture, remains underexplored. This study evaluated the mechanical properties of PLA interim crowns compared with those of polymethylmethacrylate (PMMA) and bisphenol crowns under simulated intraoral conditions with thermocycling. Three CAD/CAM polymers—PMMA (milling), PLA (fused deposition), and bisphenol (stereolithography)—were tested for fracture resistance, hardness, and surface roughness. For fracture strength, 25 crowns from each group were cemented onto dies. The Shore D hardness and surface roughness were measured on round discs before and after 10,000 thermocycles (5°C/55°C). The surface topography was assessed via scanning electron microscopy. PMMA exhibited the highest fracture strength (2787.93 N), followed by bisphenol (2165.47 N) and PLA (2088.78 N), with no significant difference between the latter two. PMMA and bisphenol showed vertical fractures and cracks, whereas PLA showed crown tearing or die deformation. Bisphenol had the highest Shore D hardness, followed by PMMA and PLA, with no significant changes after thermocycling. The surface roughness (Ra) was lowest for bisphenol and similar between PMMA and PLA. The roughness (Rz) increased from bisphenol to PMMA to PLA. The roughness of the PMMA remained unchanged after thermocycling, whereas the Ra but not the Rz of the PLA increased. Bisphenol showed a significant increase in both Ra and Rz (p<0.0001). In conclusion, PLA interim crowns demonstrated mechanical properties comparable to those of conventional PMMA and bisphenol crowns after thermocycling.